A pilot study assessing reliability and age‐related differences in corticomuscular and intramuscular coherence in ankle dorsiflexors during walking. Issue 4 (28th February 2020) - Gennaro, Federico; de Bruin, Eling D.
Abstract: Corticomuscular (CMC) and intramuscular (intraMC) coherence represent measures of corticospinal interaction. Both CMC and intraMC can be assessed during human locomotion tasks, for example, while walking. Corticospinal control of gait can deteriorate during the aging process and CMC and intraMC may represent an important monitoring means. However, it is unclear whether such assessments represent a reliable tool when performed during walking in an ecologically valid scenario and whether age‐related differences may occur. Wireless surface electroencephalography and electromyography were employed in a pilot study with young and old adults during overground walking in two separate sessions. CMC and intraMC analyses were performed in the gathered beta and lower gamma frequencies (i.e., 13–40 Hz). Significant log‐transformed coherence area was tested for intersessions test–retest reliability by determining intraclass correlation coefficient (ICC), yielding to low reliability in CMC in both younger and older adults. intraMC exclusively showed low reliability in the older adults, whereas intraMC in the younger adults revealed similar values as previously reported: test–retest reliability [ICC (95% CI): 0.44 (−0.23, 0.87); SEM : 0.46; MDC: 1.28; MDC%: 103; Hedge's g (95% CI): 0.54 (−0.13, 1.57)]. Significant differences between the age groups were observed in intraMC by either comparing the two groups with the first test [Hedge's g (95% CI): 1.55 (0.85, 2.15); p ‐value: .006] or with the retest data [Hedge's g (95% CI): 2.24 (0.73, 3.70); p ‐value: .005]. Notwithstanding the small sample size investigated, intraMC seems a moderately reliable assessment in younger adults. The further development and use of this measure in practical settings to infer corticospinal interaction in human locomotion in clinical practice is warranted and should help to refine the analysis. This necessitates involving larger sample sizes as well as including a wider number of lower limb muscles. Moreover, further research seems warranted by the observed differences in modulation mechanisms of corticospinal control of gait as ascertained by intraMC between the age groups. Abstract : Corticomuscular and intramuscular coherence are widely used nowadays in motor control and movement neurophysiology field, but it is unclear whether these assessments represent reliable tools when performed during walking in an ecologically valid scenario. Corticospinal control of gait can deteriorate during the aging process and corticomuscular or intramuscular coherence may represent an important monitoring strategy, but whether any age‐related differences may occur still needs to be elucidated. We show that neural drive to ankle dorsiflexors during gait in an ecological valid scenario is differently modulated in aging and, in parallel, we confirm previous research showing moderate reliability of intramuscular coherence, but not yet regarding corticomuscular coherence.